2020
DOI: 10.3390/life10090162
|View full text |Cite
|
Sign up to set email alerts
|

Microgravity Modulates Effects of Chemotherapeutic Drugs on Cancer Cell Migration

Abstract: Microgravity or the condition of apparent weightlessness causes bone, muscular and immune system dysfunctions in astronauts following spaceflights. These organ and system-level dysfunctions correlate with changes induced at the single cell level both by simulated microgravity on earth as well as microgravity conditions in outer space (as in the international space station). Reported changes in single bone cells, muscle cells and white blood cells include structural/morphological abnormalities, changes in gene … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 50 publications
1
23
0
Order By: Relevance
“…Prasanth et al exposed erythroleukemic and leukemic cancer cells to microgravity with RCCS for a duration of 48 h. They discovered that when leukemic cancer cells were treated with daunorubicin, they showed increased chemotactic migration ( p < 0.01) following simulated microgravity (s- μg ) compared to the normal gravity on earth (1g). This suggests that microgravity affects the response of cancer cells to chemotherapy in a drug-dependent manner [ 43 ]. There are few publications regarding the effect of chemotherapeutic drugs in a microgravity environment, which is still an open discussion with many areas for improvement.…”
Section: Studies Of the Effect Of Microgravity On Cancer Cell Linesmentioning
confidence: 99%
See 1 more Smart Citation
“…Prasanth et al exposed erythroleukemic and leukemic cancer cells to microgravity with RCCS for a duration of 48 h. They discovered that when leukemic cancer cells were treated with daunorubicin, they showed increased chemotactic migration ( p < 0.01) following simulated microgravity (s- μg ) compared to the normal gravity on earth (1g). This suggests that microgravity affects the response of cancer cells to chemotherapy in a drug-dependent manner [ 43 ]. There are few publications regarding the effect of chemotherapeutic drugs in a microgravity environment, which is still an open discussion with many areas for improvement.…”
Section: Studies Of the Effect Of Microgravity On Cancer Cell Linesmentioning
confidence: 99%
“…It has been found that resistance to chemotherapeutic drugs is reduced in tumor cell lines in microgravity environments, but this has been tested in a limited number of tumors and with only a few chemotherapeutics [ 43 ]. Currently, there are no studies in the literature examining the effect of radiotherapy in true and simulated microgravity environments.…”
Section: Therapeutic Approachesmentioning
confidence: 99%
“…Cells treated with doxorubicin showed enhanced migration both in 1 g and following μ g . The increase in ROS production in s-µ g was cell-type dependent, with acute myeloid leukaemia (AML) cells showing no increase, while chronic myeloid leukaemia (CML) cells have an increase in ROS production [ 146 ].…”
Section: Updated Knowledge On Microgravity Researchmentioning
confidence: 99%
“…So far this was the first study investigating the influence of s-µg on the effects of breast cancer treatment. However, results from leukemic cells have already indicated that s-µg is able to modulate the cancer cell response to chemotherapy [103]. Authors proposed that (s-)µg can be a powerful additional treatment for cancer cells and an immunomodulatory tool for the development of new immunotherapies, offering to open up new horizons to novel strategies for breast cancer therapy [102,103].…”
Section: Cancer Treatmentmentioning
confidence: 99%